Ulcerative Type Pyoderma Gangrenosum in Primary Sjogren's Syndrome - Şahin, Yusuf Bozkurt; Çiçek, Demet; Koca, Suleyman Serdar (My University, 2018)
Sjogren's syndrome (SjS) is a systemic chronic autoimmune disorder characterized bylymphocytic infiltrates in exocrine organs. Most patients present with the dryness of mouth, eyes,and other mucous membranes. Extracellular findings such as vasculitis and nonvascular skin findings may also occur in addition to the involvement of exocrine glands in SjS. Rarely, pyoderma gangrenosum (PG) may be present in the skin manifestations of SjS. PG is a rare, ulcerative, neutrophilicdermatosis of unclear etiology. It is associated with systemic inflammatory diseases in at least 50%of patients who are affected. We present a case report of a patient with SjS accompanied by the ulcerative type of PG in the left lower extremity.
Keywords: Dermatoloji; Genel ve Dahili Tıp